Is a Lateral Internal Sphincterotomy Necessary after Fistulotomy in a Fissure–Fistula Complex? - Sarah E. Diaz; Brittney L. Morgan; Amanda M. McClure; Jon M. Hain (World Journal of Colorectal Surgery)
Background: Fissure–fistula complex is a poorly described condition involving patients with chronic anal fissure and associated fistula-in-ano. Currently, there are no published guidelines on the surgical management of this problem. Objective: The aim of this study was to help establish guidelines for the surgical management of patients with fissure–fistula complex. Design: The study was designed as a retrospective cohort study. Setting: Data were obtained from the operative reports and medical records of patients from two colorectal surgery practices in southeast Michigan from 2000 to 2019. Patients and Methods: Forty-nine patients (47% female, 53% male) with fissure–fistula complexes were included for data analysis. The average age was 45 years. A total of 45 patients (92%) had no previous anorectal surgery, 45 (92%) had a posterior fissure complex, 26 (53%) had an intersphincteric fistula, and 23 (47%) had a low transsphincteric fistula. Although this was a retrospective study, data were described for outcomes of patients who received only a simple fistulotomy as a treatment for fissure–fistula complex. Main Outcome Measures: The primary outcome was the necessity of a lateral internal sphincterotomy after fistulotomy for resolution of the fissure. Sample Size: Forty-nine patients. Results: Three patients (6%) required repeat fistulotomy or abscess drainage during the follow-up period, and only one patient (2%) required a lateral sphincterotomy to resolve the chronic fissure. Forty-five patients (98%) healed their fissures after fistulotomy without sphincterotomy (95% confidence interval [89.1, 99.9]). Conclusions: Our study demonstrated that there is no likely need for a lateral internal sphincterotomy in addition to a fistulotomy in patients with a fissure–fistula complex for resolution of the chronic fissure. Clinical guidelines for the management of this condition should highlight primary fistulotomy as the standard treatment of fissure–fistula complex. Limitations: This study was limited by its retrospective nature and small sample size. Conflict of Interest: None.